Odzyskać raj - Stróżyna, Aneta (Kultura-Społeczeństwo-Edukacja, 2012)
The author, drawing on the metaphor of the paradise, looks at the situation of socio-cultural changes in the world. In the context of the changing reality, she especially examines the condition of a contemporary man, who participates in the world of changeable axiology. Thereby, she addresses the universalistic ethics, as a remedy for regaining the paradise.